2010
DOI: 10.1177/1460408610385516
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rupture following blunt trauma

Abstract: Cardiac rupture is the most extreme manifestation of blunt cardiac injury. In the first half of the 20th century this lesion was uniformly fatal. Since the first successful post-traumatic cardiorrhaphy by Desforges in 1955, multiple case reports and retrospective reviews have documented successful operative repair and survival of patients with this injury. Despite these successes, blunt cardiac rupture remains associated with a high mortality rate. The rarity of this condition and the heterogeneity of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…31 A more recent review found the reported incidence in patients presenting to the hospital to range from 0.05% to 0.5% and documented rare reports of survivability with early recognition and treatment, even in the setting of complex, multisystem trauma. 32 No survivors of this injury were observed in our series.…”
Section: Commentmentioning
confidence: 64%
“…31 A more recent review found the reported incidence in patients presenting to the hospital to range from 0.05% to 0.5% and documented rare reports of survivability with early recognition and treatment, even in the setting of complex, multisystem trauma. 32 No survivors of this injury were observed in our series.…”
Section: Commentmentioning
confidence: 64%
“…While the CT image can only display a hemopericardium and sometimes its compressive nature, its origin cannot be defined. In rare cases, however, an abnormal contrast material leak can be observed (3)(4)(5). Arterial…”
Section: Case Reportmentioning
confidence: 99%
“…Detection of cardiac rupture relies mainly on clinical suspicion and echocardiography, especially transesophageal echocardiography (2,3). In rare cases, leaking of the contrast material in hemopericardium patients can be detected on the initial CT examination, allowing early diagnosis of cardiac rupture (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…However, they deserve mention because of the likelihood of a catastrophic outcome and the need for immediate surgical intervention when present. These injuries may result from massive compression of the chest, traction at fixed points of attachment, or direct penetration by fractured ribs or sternum (57).…”
Section: Chest Injuriesmentioning
confidence: 99%